Scientific and patent monitoring of barley biotechnological processes for the development of antioxidant bioproducts. (Revista Brasileira Multidisciplinar, 2025)
The potential of fermented barley in the production of antioxidants, such as phenolic compounds, carotenoids, and other polyphenols, presents benefits for human health, given its capacity to mitigate oxidative stress associated with various chronic diseases such as cancer, cardiovascular diseases, neurodegenerative diseases, and others related to aging. This study examines the capacity of barley fermented through biotechnological processes to enhance antioxidant bioproducts and presents data from prospective technological studies. Using keywords, a monitoring of patents and articles was conducted on the Spacenet portals and various databases (Sciencedirect, Pubmed, Science.gov, Scopus, and Nature). A bibliometric analysis of the co-occurrences of biotechnological processes of barley related to combating oxidative stress was performed using the VOSViewer software. Based on patent and article data, advances since 2010 are highlighted, especially in combating oxidative stress, revealing progress in technologies, analytical methods, and synthesis of bioactive compounds. The intersection between science and technology underscores the importance of multidisciplinary approaches. Technological prospecting highlighted the leadership of countries such as China, the USA, and Japan, with significant contributions of commercial interest and patents in the agrochemical, food science, and pharmaceutical industries. Therefore, this study emphasized the gamification of global innovations with the growing potential of barley biotechnological processes, reflecting a trajectory at the forefront of global innovation.
Keywords: Patents; Fermentation; Beer; Oxidative Stress